Psychological Considerations in the Revision Rhinoplasty Patient - Davis, Richard E.; Bublik, Michael (Facial Plastic Surgery, 2012)
The nose contributes greatly to the facial aesthetic. Derangements in nasal cosmesis, whether from surgery, trauma, or natural causes, have a plethora of implications for the emotional well-being of the individual. Rhinoplasty and revision rhinoplasty are both facial cosmetic operations that have potentially profound cosmetic, and therefore psychological, implications for the patient. Although many revision rhinoplasty patients have hopeful yet realistic surgical expectations, there is a subset of revision rhinoplasty patients having underlying psychological disturbances that may negatively affect the surgical outcome, no matter how favorable the surgical improvement. In this article, the various psychological disorders impacting revision rhinoplasty patients will be discussed. In addition, this article will familiarize the revision rhinoplasty surgeon with many of the hallmark characteristics of psychopathology, as well as the typical emotional presentation of the well-adjusted revision rhinoplasty patient, to facilitate differentiation between these seemingly similar, but distinctly different patient groups.
Keywords: Revision rhinoplasty; psychology; personality disorders; cosmetic surgery; body dysmorphic disorder